2003
DOI: 10.1104/pp.103.021048
|View full text |Cite
|
Sign up to set email alerts
|

Expression Pattern of Two Paralogs Encoding Cinnamyl Alcohol Dehydrogenases in Arabidopsis. Isolation and Characterization of the Corresponding Mutants

Abstract: Studying Arabidopsis mutants of the phenylpropanoid pathway has unraveled several biosynthetic steps of monolignol synthesis. Most of the genes leading to monolignol synthesis have been characterized recently in this herbaceous plant, except those encoding cinnamyl alcohol dehydrogenase (CAD). We have used the complete sequencing of the Arabidopsis genome to highlight a new view of the complete CAD gene family. Among nine AtCAD genes, we have identified the two distinct paralogs AtCAD-C and AtCAD-D, which shar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
141
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 130 publications
(152 citation statements)
references
References 61 publications
10
141
0
1
Order By: Relevance
“…The analyses of wild-type Ws roots confirmed that, compared to the corresponding stem lignin, roots contain relatively less S units and correlatively more G and H units (Sibout et al, 2003), with H units contributing 5% to 7% to the total lignin thioacidolysis monomers, depending on the developmental stage of wild-type plants (Table I). Similar to stems, roots of the cyp98A3 insertion mutants provided a lower total thioacidolysis yield and a much higher proportion of H monomers (43%) compared to the wild-type roots.…”
Section: Cyp98a3 T-dna Insertion and Cosuppression Mutants Show Drastmentioning
confidence: 66%
“…The analyses of wild-type Ws roots confirmed that, compared to the corresponding stem lignin, roots contain relatively less S units and correlatively more G and H units (Sibout et al, 2003), with H units contributing 5% to 7% to the total lignin thioacidolysis monomers, depending on the developmental stage of wild-type plants (Table I). Similar to stems, roots of the cyp98A3 insertion mutants provided a lower total thioacidolysis yield and a much higher proportion of H monomers (43%) compared to the wild-type roots.…”
Section: Cyp98a3 T-dna Insertion and Cosuppression Mutants Show Drastmentioning
confidence: 66%
“…The supernatant was decanted and about 20 lg of total proteins were used for the CAD and SAD activity assays. Assays of crude enzyme were carried out in the reverse direction using coniferyl alcohol and sinapyl alcohol as the substrates, and the formation of hydroxy-cinnamaldehydes was monitored spectrophotometrically (DU640; Backman, Fullerton, USA) at 400 nm using the following molar extinction coefficients: coniferaldehyde 2.10 9 10 -4 M -1 cm -1 and sinapaldehyde 1.68 9 10 -4 M -1 cm -1 , as described by Sibout et al (2003). Assays were carried out at 30°C for 10 min in 100 ll of 100 mM Tris-HCl (pH 8.8), 100 lM NADP, and 250 lM coniferyl alcohol or sinapyl alcohol.…”
Section: Measurement Of Cell Wall Compositionmentioning
confidence: 99%
“…1.195) is an enzyme in the lignin biosynthetic pathway that catalyzes the final reduction of the hydroxyl-cinnamaldehydes to the corresponding alcohols (Mansell et al 1974). The relative proportions of these cinnamyl alcohols are important factors that determine the structural and mechanical properties of lignin (Mellerowicz et al 2001;Sibout et al 2003). CAD genes in different species display distinct features depending on their phylogenetic origin.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Atcad-c and Atcad-d mutants of Arabidopsis have reduced CAD activities, but only Atcad-d shows a (slight) reduction in lignin content, reduction of S units and incorporation of sinapaldehyde in lignin (Sibout et al, 2003). According to Kim et al, (2004), CAD mutants of Arabidopsis attain wild-type lignin levels and composition by maturity.…”
Section: Cinnamyl Alcohol Dehydrogenasementioning
confidence: 99%